Evaluating the utilisation of Climate-Smart Agriculture (CSA) technologies and practices among smallholder farmers in The Lawra, Jirapa and Nandom districts of Ghana - Sam, Kingsley Odum; Botchway, Vincent Ansah; Karbo, N; Essegbey, George Owusu; Nutsukpo, Delali Kofi; Zougmoré, Robert B. (African Journals Online, 2020)
Climate change is posing threat to agriculture in sub-Saharan Africa including Ghana. Climate-Smart Agriculture (CSA) is proposed to solve climate change impacts on agriculture. Smallholder farmers are adopting various strategies to be resilient to climate change effects. Empirical research is required to evaluate CSA utilisation in Ghana. Lawra, Jirapa and Nandom districts in the climate-risk areas of Guinea Savannah agro-ecological zone were chosen and Participatory Rapid Appraisal (PRA) tools were used. Farm budget analysis and market price methods were employed; key financial decision-making tools were net returns, profit margins and benefit-cost ratio. Soft systems content analysis, frequencies, means, ranking and data aggregation were employed to generate results. CSA use in the study districts was smallholder driven and male dominated. CSA was mainly used for staples including cereals and legumes and small ruminants under livestock. Crop-livestock integration and crop rotation were the common CSA practices with the highest costs (GH¢6,370.00) and highest revenues (GH¢9,460.00) respectively. Utilisation of CSA in the districts is beneficial and investments are profitable and financially viable. All actors and stakeholders must join forces to promote CSA in the districts. Rigorous promotional campaigns, capacity building and funding at all levels are crucial for CSA adoption in Ghana.